'Fine‐tuning' blood flow to the exercising muscle with advancing age: an update. Issue 6 (13th May 2015) - Wray, D. Walter; Richardson, Russell S.
<x xml:space="preserve">Abstract</x> New Findings What is the topic of this review? This review focuses on age‐related changes in the regulatory pathways that exist at the unique interface between the vascular smooth muscle and the endothelium of the skeletal muscle vasculature, and how these changes contribute to impairments in exercising skeletal muscle blood flow in the elderly. What advances does it highlight? Several recent in vivo human studies from our group and others are highlighted that have examined age‐related changes in nitric oxide, endothelin‐1, alpha adrenergic, and renin‐angiotensin‐aldosterone (RAAS) signaling. During dynamic exercise, oxygen demand from the exercising muscle is dramatically elevated, requiring a marked increase in skeletal muscle blood flow that is accomplished through a combination of systemic sympathoexcitation and local metabolic vasodilatation. With advancing age, the balance between these factors appears to be disrupted in favour of vasoconstriction, leading to an impairment in exercising skeletal muscle blood flow in the elderly. This 'hot topic' review aims to provide an update to our current knowledge of age‐related changes in the neural and local mechanisms that contribute to this 'fine‐tuning' of blood flow during exercise. The focus is on results from recent human studies that have adopted a reductionist approach to explore how age‐related changes in both vasodilators (nitric oxide) and vasoconstrictors (endothelin‐1, α‐adrenergic agonists and angiotensin II) interact and how these changes impact blood flow to the exercising skeletal muscle with advancing age.